2015
DOI: 10.1002/adma.201503163
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Tuning of 2D MoS2 through Surface Functionalization

Abstract: The electronic properties of thiol-functionalized 2D MoS2 nanosheets are investigated. Shifts in the valence and conduction bands and Fermi levels are observed while bandgaps remain unaffected. These findings allow the tuning of energy barriers between 2D MoS2 and other materials, which can lead to improved control over 2D MoS2 -based electronic and optical devices and catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
200
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(211 citation statements)
references
References 39 publications
6
200
1
1
Order By: Relevance
“…In the present work, ultraviolet photoelectron spectroscopy (UPS) spectra were obtained to determine the absolute valence band position of FeIn 2 S 4 , and XPS spectra were acquired to determine the difference between the Fermi level and the valence band of FeIn 2 S 4 ( Figure 4 ). 20 Regarding band alignment in a device, to understand the charge carrier transport mechanism, it is important to establish the exact Fermi level of the semiconducting material. According to UPS spectra obtained using He I excitation (21.2 eV), the valence band position of FeIn 2 S 4 appeared to be around −5.2 eV, with a high‐energy cutoff of 16 eV (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, ultraviolet photoelectron spectroscopy (UPS) spectra were obtained to determine the absolute valence band position of FeIn 2 S 4 , and XPS spectra were acquired to determine the difference between the Fermi level and the valence band of FeIn 2 S 4 ( Figure 4 ). 20 Regarding band alignment in a device, to understand the charge carrier transport mechanism, it is important to establish the exact Fermi level of the semiconducting material. According to UPS spectra obtained using He I excitation (21.2 eV), the valence band position of FeIn 2 S 4 appeared to be around −5.2 eV, with a high‐energy cutoff of 16 eV (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, despite the progress achieved so far targeting the exfoliation of MoS 2 , its covalent functionalization is still hampered. In fact, the limited functionalization procedures reported to date mainly utilize exfoliated MoS 2 by n-butyl lithium (n-BuLi), thus of the metallic polytype 1T-MoS 2 in which the negative charges on MoS 2 due to charge-transfer from n-BuLi, are quenched by alkyl halides, 24 and diazonium salts, 22 while thiols are conjugated at sulfur vacancies 21,[25][26][27][28] and metal carboxylate salts coordinate to surface sulfur atoms of 2H-MoS 2 . 29 Therefore, it is absolutely desirable and timely to functionalize semiconducting MoS 2 species with organic electron donor units.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we disclose the location ("where") and the manner ("how") this functionalization occurs based on density functional theoretical studies supported by X-ray photoelectron spectroscopy (XPS) and confirmed by high-resolution transmission electron microscopy (HRTEM) imaging and electron energy loss 2 and preserving to great extent their novel surface properties, as well as their semiconducting character, while also allows the incorporation of a plethora of suitably modified organic derivatives targeting diverse applications. Importantly, the presence of defects at the edges of MoS 2 , as generated by either chemical exfoliation 21,[25][26][27][28] or ion irradiation, 32 guarantees the universal utility and versatility of the functionalization route. The newly prepared MoS 2 -based nanohybrids were fully characterized, while examination of the optical properties revealed the occurrence of significant electronic interactions in the MoS 2 -pyrene 2b hybrid.…”
Section: Introductionmentioning
confidence: 99%
“…[8] In contrast to graphene,reports on the covalent functionalization of TMDs remain scarce. [6,8,10] Ultrathin MoS 2 nanosheets are excellent candidates for constructing hybrids with high specific surface area and high flexibility. [6,8,10] Ultrathin MoS 2 nanosheets are excellent candidates for constructing hybrids with high specific surface area and high flexibility.…”
mentioning
confidence: 99%